(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
In this paper, a tensorial method was used in computing the intensity of Ultra High Frequency(UHF) radiation within 2D and 3D geometrical structures. This was done based on the theoretical concepts of classical electromagnetism. Using a software program, “power estimator” the intensities at various distances from the source of radiation were obtained and it was found that shapes which are less geometrically homogenous exhibits high intensity values and that the maximum intensity value was observed within a cylinder to be 1534.70w/m² at 0.02m away from the source of radiation, while the minimum intensity value was observed in a circle at 0.10m away from the source to be 2.49w/m².